2020
DOI: 10.1101/2020.02.14.950022
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alterations in the intrinsic properties of striatal cholinergic interneurons after dopamine lesion and chronic L-DOPA

Abstract: Changes in striatal cholinergic interneuron (ChI) activity are thought to contribute to Parkinson's disease pathophysiology and dyskinesia from chronic L-3,4-dihydroxyphenylalanine (L-DOPA) treatment, but the physiological basis of these changes are unknown. We find that dopamine lesion decreases the spontaneous firing rate of ChIs, whereas chronic treatment with L-DOPA of lesioned mice increases baseline ChI firing rates to levels beyond normal activity. The effect of dopamine loss on ChIs was due to decrease… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Cell-attached and whole-cell recordings were accomplished using glass pipettes (2-6 MV) filled with internal solution: 115 mM potassium gluconate, 20 mM KCl, 20 mM HEPES, 1 mM MgCl 2 , 2 mM MgATP, and 0.2 mM Na 2 GTP adjusted to pH 7.25 with KOH, osmolarity 285 mOsm (Choi et al, 2020). Spontaneous firing frequency in cell-attached mode was recorded for 3 min.…”
Section: Electrophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-attached and whole-cell recordings were accomplished using glass pipettes (2-6 MV) filled with internal solution: 115 mM potassium gluconate, 20 mM KCl, 20 mM HEPES, 1 mM MgCl 2 , 2 mM MgATP, and 0.2 mM Na 2 GTP adjusted to pH 7.25 with KOH, osmolarity 285 mOsm (Choi et al, 2020). Spontaneous firing frequency in cell-attached mode was recorded for 3 min.…”
Section: Electrophysiologymentioning
confidence: 99%
“…I h was quantified as reported in (Choi et al, 2020). Hyperpolarizing steps (À10 to À90 mV) from holding potential (À60 mV) were held for 1 s, and the current difference across the voltage step was quantified.…”
Section: Voltage Clamp Experimentsmentioning
confidence: 99%
“…17 However, ex vivo studies in rodent models of PD have found no or modest changes of intrinsic tonic activity in SCINs 14,18,19 that can be partially reverted by L-dopa treatment. 20 Because PD becomes seriously debilitating when motor fluctuations and LID emerge, detailed studies in the off-state of L-dopa medication are needed. If chronic L-dopa exposure further disrupts SCIN activity in this condition, then SCIN potential as a therapeutic target to treat PD and LID increases.…”
mentioning
confidence: 99%
“…In vivo studies found that striatal tonically active neurons (putative SCINs) exhibit enhanced spontaneous oscillatory activity in parkinsonian monkeys that persists during the off‐state of l ‐dopa medication 17 . However, ex vivo studies in rodent models of PD have found no or modest changes of intrinsic tonic activity in SCINs 14,18,19 that can be partially reverted by l ‐dopa treatment 20 . Because PD becomes seriously debilitating when motor fluctuations and LID emerge, detailed studies in the off‐state of l ‐dopa medication are needed.…”
mentioning
confidence: 99%
“…The universality and nonselective cation permeability make HCN channels indispensable for cell excitability. Not only in pyramidal neurons, interneurons excitability homeostasis disorder also can trigger psychosis [51,52]. Simultaneously, HCN channels engage on intracellular coupling reaction, such as alpha-2 (α 2 ) adrenergic receptor, and the location of HCN channels in post-synapse membrane also facilitates their involvement in synaptic signaling [28].…”
Section: Discussionmentioning
confidence: 99%